The Stripe Fortified GCT: A new GCT design for maximizing the controllable current - Lophitis, Neophytos; Antoniou, M.; Udrea, F.; Nistor, I.; Arnold, M.; Wikstrom, T.; Vobecky, J.; Rahimo, M. (My University, 2014)
In this paper we introduce a new GCT design, namely the Stripe Fortified GCT, for the purpose of maximizing the controllable current by optimizing the current flow path in the device during turn-off. The main design of the new device along with variants are introduced. The MCC performance of this novel structure is assessed with a developed two dimensional model for full wafer simulations. Our results show that this new design is a very good candidate for increasing the MCC to values more than 5000A. © 2014 IEEE.
Keywords: Computer simulation; Current flows; New devices; Novel structures; Turn offs; Two dimensional model